METODE TAKRIR DALAM MENGHAFAL AL-QUR AN DI PONDOK PESANTREN MADRASATUL QUR AN TEBUIRENG JOMBANG - Suhari; Muhammad Basarrudin; Moh. Slamet; Muhammad Ghozali; Dewi Sulistiawati (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2022)
This article discusses the Takrir Method in Memorizing the Qur'an at Madrasatul Qur'an Islamic Boarding School Tebuireng Jombang. This research is a qualitative research with a naturalistic approach. The data collection techniques in this study are: (1) observation, (2) interviews, and (3) documentation. Sources of data in this study were caregivers, ustad, documents, and other related parties. This research resulted in several findings, as follows: 1) The Takrir method in the Madrasatul Qur'an Islamic Boarding School has been going well, namely the students deposit their memorization to the ustad or badal who has been appointed directly by the caretaker. Before depositing their memorization, the students prepare their memorization by assessing (repeating) their memorization either by themselves or asking their friends to accept the memorization that will be deposited. At night, the santri do the mudarosah activity which consists of three people, one person reads his memorization, two people listen and take turns. However, it is not perfect yet with some obstacles. 2) The inhibiting factor that is felt by the student is that the student have difficulty managing time because the santri have two obligations, namely memorizing and going to school and for pure tahfid students they feel that they have a lot of time so that they delay and feel there is time later to evaluate memorization, not realizing the benefits of assessing their memorization when it is time in group mudarosah activities where students should evaluate their memorization in groups but in reality students tend to evaluate their memorization individually, and there is a lack of istiqomah in students in assessing their memorization. 3) Supporting factors include: the existence of adequate infrastructure facilities, and policies from caregivers in terms of developing the creativity of ustadz and students with guidance in the scientific field, reading fashohah, coaching management, and Qiro'ah coaching for students. 4) The solution to overcoming the inhibiting factors is by managing time, taking attendance for memorizing students by means that every time students will deposit their memorization they must bring a report card and submit it to the ustad and the report card will be evaluated once a month and their memorization will be evaluated once every four months. So that this solution can overcome the inhibiting factors of the takrir method in memorizing the Qur'an in PP.MQ